2017
DOI: 10.1016/j.jsams.2017.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Misunderstandings of concussion within a youth rugby population

Abstract: Objectives: The recognition and management of concussion has become a major health concern within rugby union. Identifying misconceptions and attitudes regarding concussion is valuable for informing player education. Therefore, the purpose of this study was to explore the knowledge of, and attitudes towards, concussion in subgroups of youth rugby players. Design: Cross-sectional survey. Methods: Information sheets and consent forms were distributed at training sessions for multiple teams at each of three schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
3
20
1
Order By: Relevance
“…As in the present study, the Shuttleworth-Edwards [32] study found the most frequently reported symptoms to include headache, fatigue, balance problems, concentration, dizziness, light sensitivity and sleeping problems. These findings are in line with international research studies by Brooks et al; [2] Kearney et al; [4] Marar et al [33] and Green et al [34] which showed that at three months post injury, high school athletes were still reporting more symptoms of headache, dizziness and poor concentration compared with controls, illustrating prolonged effects in high school athletes. These persisting symptoms could have severe effects on an individual's daily activities, including ability to work and attend school, function independently at home, or develop and maintain appropriate social relations.…”
Section: Researchsupporting
confidence: 89%
“…As in the present study, the Shuttleworth-Edwards [32] study found the most frequently reported symptoms to include headache, fatigue, balance problems, concentration, dizziness, light sensitivity and sleeping problems. These findings are in line with international research studies by Brooks et al; [2] Kearney et al; [4] Marar et al [33] and Green et al [34] which showed that at three months post injury, high school athletes were still reporting more symptoms of headache, dizziness and poor concentration compared with controls, illustrating prolonged effects in high school athletes. These persisting symptoms could have severe effects on an individual's daily activities, including ability to work and attend school, function independently at home, or develop and maintain appropriate social relations.…”
Section: Researchsupporting
confidence: 89%
“…Reasons for players not seeking treatment for concussions (and thus not making a claim) may include lack of recognition of the injury by the injured player or their family or teammates, or a belief that the injury is of insufficient severity to require presentation to medical providers [34][35][36]. For injuries other than concussion, players can return to play when they or their guardians see fit, either in conjunction with or independent of medical advice.…”
Section: Concussion/brain Injurymentioning
confidence: 99%
“…12,13 Important misunderstandings about concussion have been identified, for example, one study revealed that 80% of youth rugby players believed that there needed to be a direct hit to the head to sustain a concussion. 14 Despite the high prevalence of concussion in equestrian sports, little is known about concussion awareness in those engaging in activities involving horses.…”
Section: Introductionmentioning
confidence: 99%